Identification, characterization and preliminary X‐ray diffraction analysis of the rolling‐circle replication initiator protein from plasmid pSTK1. Issue 10 (8th October 2013) - Carr, Stephen B.; Mecia, Lauren B.; Phillips, Simon E. V.; Thomas, Christopher D.
<x xml:space="preserve">Abstract</x> Antibiotic resistance in bacterial pathogens poses an ever‐increasing risk to human health. In antibiotic‐resistant strains of Staphylococcus aureus this resistance often resides in extra‐chromosomal plasmids, such as those of the pT181 family, which replicate via a rolling‐circle mechanism mediated by a plasmid‐encoded replication initiation protein. Currently, there is no structural information available for the pT181‐family Rep proteins. Here, the crystallization of a catalytically active fragment of a homologous replication initiation protein from the thermophile Geobacillus stearothermophilus responsible for the replication of plasmid pSTK1 is reported. Crystals of the RepSTK1 fragment diffracted to a resolution of 2.5 Å and belonged to space group P212121.